Kingdom of the Netherlands-Netherlands : Technical Note; The Netherlands Model of Financial Sector Supervision. (IMF Staff Country Reports; Country Report ;, 2004)
This technical note on the Kingdom of the Netherlands-Netherlands reviews the Model of Financial Sector Supervision. The Netherlands authorities have invested considerable thought and effort in designing and implementing the new institutional framework, and we expect that it will make an important contribution to ensuring continued effective supervision as the financial system evolves further. The framework of financial sector supervision in the Netherlands is in the process of transformating from a fairly traditional sectoral approach to a cross-sectoral functional approach.